KOMPOSISI KIMIA DAN AKTIVITAS ANTIBAKTERI MINYAK ATSIRI Piper gibbilimbum C. DC.: PIPERACEAE - Praptiwi; Yuliasri Jamal; Ahmad Fathoni; Ary P. Keim (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2011)
Distillation of Piper gibilimbum leaves by water distillation yielded 0.85% light yellow essential oil. Result of GC-MS analyses showed that P. gibilimbum essential oil contained 72 chemical compounds with major components 3-carene (40.64%), β -pinene (8.47%), cineol (6.19%), α-copaene (5.47%) and α-guaiene (9.30%). Antibacterial test with disc paper method indicated that the essential oil at 50% concentration inhibited the growth of Staphylococcus aureus, Bacillus subtilis, Streptococcus mutans, Streptococus viridans, Escherisia coli and Shigella flexneri.